Pengaruh literasi keuangan, experienced regret, risk tolerance, dan motivasi pada keputusan investasi keluarga dalam perspektif masyarakat Bali - Astri Kusuma Wardani; Lutfi Lutfi (Journal of Business & Banking, 2016)
This study aims to determine the effect of financial literacy, experienced regret, risk tolerance, and motivation on family investment decisions by taking samples of 105 Balinese residents. The investment decision investigated in this study is dealt with the decision to invest the money in capital market instruments and bank accounts. The analytical method used is a quantitative method using multiple linear regressions. The data were collected using a survey of questionnaire to the respondent. The sampling technique used is purposive sampling method and then continued using convenience sampling. The results of this study indicate that risk tolerance has positive influence on investment decisions of Balinese family. Meanwhile, financial literacy, experienced regret, and motivation do not affect significantly investment decisions of Balinese family. These results imply that Balinese people consider their risk tolerance as the main factor considered in making decision whether to put the money in bank accounts or capital market instruments.